Macrolíquenes Cortícolas en Dos Especies de Coníferas del Parque Nacional Lagunas de Zempoala - Pérez-Pérez, Rosa Emilia; Miramontes-Rojas, Noemí; Aguilar-Rosales, Jehtro; Quiroz-Castelán, Héctor (Acta Universitaria, 2008)
In this study communities of corticolous macrolichens and their relationship to the structure of the forest in areas with Abies religiosa and Pinus ayacahuite were analyzed. 33 species were collected, 25 in A. religiosa and 20 in P. ayacahuite, with significant differences in lichens species number and covered among the different heights and orientations of the trees, similarly results were obtained with the randomized block experimental design, which indicated significant differences among heights and orientations of the trees in A. religiosa, while in P. ayacahuite only orientation is significant. At these sites, a patchwork of heterogeneous patches have been induced with different ecological and micro-climatic characteristics, affecting the distribution of macrolichens. The A. religiosa forest can be considered as a mature forest and the P. ayacahuite as a disturbed forest, which makes the dispersal, establishment and maintenance of lichens communities difficult.
Keywords: Array; Array; Array